IMPLEMENTASI KEBIJAKAN ANGGARAN DANA DESA BERDASARKAN UU NO 6 TAHUN 2014 TENTANG DESA (Studi Kasus Desa Songan B, Kintamani, Bangli) - Santiasih, Santiasih (CITIZEN CHARTER, 2017)
Village funds is a fund provided by the central government to villages which transferred from state budget revenues and expenditures. By the village funds, it expected to increase development and reduce the level of poverty in the village. Songan B Village Kintamani Sub-district Bangli Regency is one of some villages that receive the largest amount of Village Fund in Bangli Regency, but the large funding is not balanced by the availability of adequate human resources, lack of budget transparency to the community, and lack of understanding of the village apparatus regarding Regulation of the rules of the village funds themselves. This research was conducted by a qualitative descriptive method with data collection technique in depth interview with the informant. This study measures how is the implementation of village budget policy based on law number 6 the year 2014 about the village (case study in Songan B Village Kintamani District Bangli district) with the theory of public policy implementation (George C. Edward III) consisting of communication indicators, disposition, resources, and bureaucratic structure. The results of this study indicate that the implementation of village budget fund policy in Songan B Village has not been optimum yet because of the lack of clarity of information, lack of understanding of the apparatus concerning their respective tasks, lack of human resources in using the computer, and still lack of understanding of the apparatus regarding the rules that apply to the management village funds. Keywords: Public policy, Policy implementation, Village funds